2022
DOI: 10.3340/jkns.2021.0199
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Pathologic Vertebral Fractures in Multiple Myeloma : Propensity Score Matched Cohort Study between Reconstructive Surgery with Adjuvant Radiotherapy and Radiotherapy Alone

Abstract: Objective : Although radiotherapy (RT) is recommended for multiple myeloma (MM) involving spine, the treatment of choice between reconstructive surgery with RT and RT alone for pathologic vertebral fractures (PVFs) associated with structural instability or neurologic compromises remains controversial. The purpose of this study was to evaluate the clinical efficacies of reconstructive surgery with adjuvant RT for treatment of MM with PVFs by comparing with matched cohorts treated with RT alone. Methods : Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Although a direct comparison of neurologic recovery between the surgery group and RT alone group was not possible due to different neurologic statuses before the treatment, a previous study reported that relief of Frankel grade in the surgery group was superior to that of the radiotherapy group (p = 0.025) in treating spinal metastasis of lung cancer [27]. In the pathologic vertebral fracture in multiple myeloma, we also reported that spinal surgery might provide better clinical outcomes than RT alone in maintaining independent ambulation, neurological status, and pain control despite similar median survival and complications [28].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although a direct comparison of neurologic recovery between the surgery group and RT alone group was not possible due to different neurologic statuses before the treatment, a previous study reported that relief of Frankel grade in the surgery group was superior to that of the radiotherapy group (p = 0.025) in treating spinal metastasis of lung cancer [27]. In the pathologic vertebral fracture in multiple myeloma, we also reported that spinal surgery might provide better clinical outcomes than RT alone in maintaining independent ambulation, neurological status, and pain control despite similar median survival and complications [28].…”
Section: Discussionmentioning
confidence: 59%
“…This result was consistent with our previous report regarding multiple myeloma. In patients with unstable pathologic vertebral fractures due to multiple myeloma, spinal surgery with adjuvant RT compared with RT alone provided better clinical outcomes in terms of maintaining independent ambulation and neurologic status despite similar median survival and complications [28]. In this regard, surgery for the MSD of lung cancer should be considered for cases of potentially unstable spine and neurological deficits that can be resolved by direct decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis results demonstrated that preoperative KPS and ECOG-PS scores were factors influencing patient prognosis. It is evident that postoperative records better reflect patient prognosis [ 55 ]. However, considering that the purpose of this study was to provide references for preoperative decision-making, the KPS and ECOG-PS values included preoperative records, unavoidably reducing the predictive accuracy of these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, KPS showed meaningful statistical results. The lower the KPS and the higher the ECOG-PS score, the worse the prognosis of the patients [ 27 , 55 ]. Currently, ECOG has been proven to be associated with an increased risk of infection in patients with MM and has been incorporated into the infection risk prediction models for MM patients, such as the FIRST and GEM-PETHEMA models [ 56 ].…”
Section: Discussionmentioning
confidence: 99%